A Critical Analysis of Falsification as Fraud - Carroll, La Shun L. (ETHICS IN PROGRESS, 2024)
This paper critically evaluates the classification of research-related fraudulent activities, with an emphasis on the specific misconduct falsification. The analysis begins by interrogating the assumption that all acts of fraud in research are intentional, suggesting that some instances may inadvertently arise during the course of scholarly activities. Misconducts like fabrication and falsification are categorized as fraudulent primarily due to their generation during research activities and their direct contribution to the distortion of scientific knowledge. Plagiarism, while deceptive, does not necessarily originate from the research process nor lead directly to such distortion, and therefore is not classified as de facto fraud. The paper proposes that the definition of falsification – as established by the PHS – requires refinement to prevent wrongful allegations and convictions, enhance transparency, and offer clearer guidelines. This nuanced understanding is vital for safeguarding the credibility of the research process and protecting scientists from unfounded career-damaging accusations. Ultimately, this paper advocates for a clearer definition of falsification to protect the integrity of scientific research and prevent the miscarriage of justice.